Effects of habitat loss on the genetic diversity of Embiratermes neotenicus (Isoptera) in a fragmented landscape of the Atlantic Forest, Brazil. Issue 4 (10th March 2020) - Vieira de Oliveira Couto, Alane Ayana; Hellemans, Simon; Roisin, Yves; Montes, Martín Alejandro; Vasconcellos, Alexandre
Abstract: Connectivity loss during habitat fragmentation poses a serious threat to global biodiversity. The effects of this process depend on factors such as the dispersal ability and breeding systems of each species, the type of land use surrounding the habitat remnants and the position of fragments in the landscape. Termites are abundant in tropical ecosystems, and within this group, soil‐feeding species are the most sensitive to environmental degradation. We investigated whether the fragmentation of the Atlantic Forest that occurred approximately 110 years ago because of sugarcane plantations in Northeast Brazil affected the genetic diversity of a population of Embiratermes neotenicus (Termitidae: Syntermitinae) in 14 fragments separated by 3–104 m over an extent of 20 km. For 10 nests in each fragment, 10 individuals ( n = 1400) were genotyped at five microsatellite loci. Our results show that the population exhibits weak genetic structure, with no relations between genetic variability and fragment features. This result may be explained by the extraordinarily long lifespan of individual colonies, given this species' peculiar breeding system, offering several opportunities for dispersal events and patch colonisation. Landscape features such as the arrangement of forest fragments and seasonal nature of the sugarcane matrix could enable this species to maximise dispersal success and avoid local extinction. Abstract : The fragmentation of the Atlantic Forest that occurred because of sugarcane plantations did not affect the genetic diversity of a population of Embiratermes neotenicus (Termitidae: Syntermitinae). This result may be explained by the extraordinarily long lifespan of individual colonies, given this species' peculiar breeding system, offering several opportunities for dispersal events and patch colonisation. Landscape features such as the arrangement of forest fragments and seasonal nature of the sugarcane matrix could enable this species to maximise dispersal success and avoid local extinction.